Specimens of Convolvulaceae linked to the plates of Dillenius's Hortus Elthamensis - Wood, J; Marner, S; Scotland, R; Harris, S (International Association for Plant Taxonomy, 2018)
Dillenius's Hortus Elthamensis was published in 1732. In most versions the plates are uncoloured, but a few surviving coloured versions are known. The plates are of considerable historical and scientific importance as many Linnaean types are founded on these illustrations. The specimens on which the plates were based are still housed in the Oxford University Herbaria (OXF) and examples from Convolvulaceae are discussed to show how the plates were based on and sometimes copied exactly from the original specimens. A second-step lectotypification is made for Ipomoea glaucifolia. Our study of Convolvulaceae types highlights the value of consulting corresponding specimens in other families when interpreting ambiguous types based on plates in Hortus Elthamensis.